2022
DOI: 10.1001/jamaneurol.2022.2977
|View full text |Cite
|
Sign up to set email alerts
|

Cancer Risk in Children of Mothers With Epilepsy and High-Dose Folic Acid Use During Pregnancy

Abstract: ImportanceWomen with epilepsy are recommended high doses of folic acid before and during pregnancy owing to risk of congenital anomalies associated with antiseizure medications. Whether prenatal exposure to high-dose folic acid is associated with increases in the risk of childhood cancer is unknown.ObjectiveTo assess whether high-dose folic acid supplementation in mothers with epilepsy is associated with childhood cancer.Design, Setting, and ParticipantsObservational cohort study conducted with nationwide regi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
35
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 36 publications
(69 reference statements)
0
35
0
Order By: Relevance
“…The headline from the recent manuscript by Vegrim and colleagues 1 caused a collective gasp among providers who specialize in the treatment of persons with epilepsy and gestational capacity (PWEGC). In this study from the Nordic Register-Based Study of Antiepileptic Drugs in Pregnancy (SCAN-AED) collaboration, the authors report an association between “high-dose” folic prescriptions to pregnant patients with epilepsy and an increased risk of childhood cancer in their children.…”
Section: Commentarymentioning
confidence: 99%
“…The headline from the recent manuscript by Vegrim and colleagues 1 caused a collective gasp among providers who specialize in the treatment of persons with epilepsy and gestational capacity (PWEGC). In this study from the Nordic Register-Based Study of Antiepileptic Drugs in Pregnancy (SCAN-AED) collaboration, the authors report an association between “high-dose” folic prescriptions to pregnant patients with epilepsy and an increased risk of childhood cancer in their children.…”
Section: Commentarymentioning
confidence: 99%
“…28 A recent analysis of more than 27 000 pregnancies among PWECP, on the other hand, demonstrated that folic acid supplementation greater than 1 mg per day was associated with a close to 3-fold increase in the instantaneous risk of childhood cancer (although the absolute risk remained less than 2%). 29 Recognizing that some ASMs, notably valproic acid may have increased negative pregnancy outcomes is necessary to consider when treating PWECP. Many PWECP in the United States will now have limited options should they be faced with adverse consequences of ASM treatment in pregnancy.…”
Section: Impact Of Anti-seizure Medications On Teratogenicity and Adv...mentioning
confidence: 99%
“…In Reply We thank Voinescu and colleagues for their comments on our recent article in JAMA Neurology . We agree that there is no study to date to help in determining the optimal dose of folic acid supplementation for women with epilepsy.…”
mentioning
confidence: 99%